[Tobacco Institute StateLine report] - #Error (Tufts Archival Research Center, 2007)
Tobacco Institute StateLine report. Reports state headlines on tobacco legislation and its status. Discusses taxes, initiatives and referenda, and smoking restrictions. Adresses employment discrimination, advertising and sales restrictions, and packaging and litter. Looks at local activity.